Perceived built environments correlated to route choice for healthy leisure walking - Eun Jung Kim; Youngeun Gong (Journal of Asian Architecture and Building Engineering, 2025)
This study aimed to identify the environmental factors of pedestrians’ preferred route and examine which factors are related to the choice of a healthy route. This study set the shortest and healthy routes in Ayanggyo neighborhood in Daegu Metropolitan City, South Korea. A healthy route is longer than the shortest route but has rich greenery and low traffic. A survey of 203 respondents was conducted from October 12 to 8 November 2022. This study used a logistic regression model with a walking route choice as the dependent variable. Results showed that 65% of participants chose a healthy route. People who considered low noise levels, presence of greenery and waterfront areas, low traffic speed, and presence of traffic safety facilities as important were likelier to choose healthy routes. The results suggest that pleasant and safe routes and built environments can make people walk longer. The findings of this study provide evidence to urban planners and policymakers that the built environmental conditions play an important role in encouraging residents’ walking behavior. This can contribute to urban policies supporting citizens’ active and healthy walking.